2013
DOI: 10.1166/jbn.2013.1643
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Layer Composite Dressing of Gelatin Nanofibrous Mat and Poly Vinyl Alcohol Hydrogel for Drug Delivery and Wound Healing Application:<I>In-Vitro</I> and <I>In-Vivo</I> Studies

Abstract: Present investigation involves the development of a bi-layer dressing of gelatin nanofibrous mat loaded with epigallocatechin gallate (EGCG)/poly vinyl alcohol (PVA) hydrogel and its in-vivo evaluation on full-thickness excision wounds in experimental Wistar rats. Nanomorphological observation, porosity, effect of crosslinking on tensile strength, physical stability and drug release profile in phosphate buffer and biocompatibility aspects of electrospun nanomat were investigated by various physico-chemical too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Electrospun nanofibers were found to be very effective to be used as the wound dressing material mainly due to its architectural superiority. The electrospun nanofiber can mimic the extra cellular matrix (ECM) environment which will help the host cells to grow and create a new natural cellular matrix [21,22]. Most importantly the preferred therapeutic materials can be introduced to the nanofiber matrix using the electrospinning process [17,23,24], that can seriously affect the wound healing.…”
Section: Q2mentioning
confidence: 99%
“…Electrospun nanofibers were found to be very effective to be used as the wound dressing material mainly due to its architectural superiority. The electrospun nanofiber can mimic the extra cellular matrix (ECM) environment which will help the host cells to grow and create a new natural cellular matrix [21,22]. Most importantly the preferred therapeutic materials can be introduced to the nanofiber matrix using the electrospinning process [17,23,24], that can seriously affect the wound healing.…”
Section: Q2mentioning
confidence: 99%
“…An interesting study by Jaiswal et al has shown that poly(vinyl alcohol) hydrogel impregnated with epigallocatechin gallate is very effective in healing wounds by improving angiogenesis, restoring epithelialization, and decreasing the inflammatory response. 52 …”
Section: Hydrogelsmentioning
confidence: 99%
“…Electrospun NFs have large surface area to volume ratio, which improves the drug‐loading capacity and mass transfer properties of the medicated mats. In addition, electrospun dressings can provide a controlled drug release profile ranging from minutes to months depending on the application, design, and material system …”
Section: Introductionmentioning
confidence: 99%